Tailored adsorption of enzymes onto mesoporous silicates - Gaffney, Darragh (University of Limerick, 2010)
peer-reviewed The objective of this research is to synthesise mesoporous silicates, incorporate metal complexes on to the surface of the silicates post synthesis and utilise these materials for the immobilisation of histidine-tagged enzymes to form stable, reusable biocatalysts. Studies in the synthesis of a range of mesoporous silicates and subsequent postsynthetic metal-cyclam functionalisation are presented. The generation of nickel-cyclam functionalised MCM-41/89, SBA-15 and MCF was successfully achieved in good yield. Post-synthetic methods for the metal-cyclam functionalisation of the mesoporous silicate mesocellular foam (MCF) are presented and compared. MCF functionalised using a one-pot functionalisation technique had a higher metal content than a step-wise functionalisation technique. Optimisation steps were required for the specific adsorption of histidine tagged proteins/enzymes onto metal functionalised mesoporous silicates. As a proof-of-concept system, the immobilisation of the histidine-tagged inhibitor protein Spi onto SBA-15- Ni-cyclam was investigated. Optimisation of the immobilisation using varying concentrations of NaCl and PEG400 demonstrated specific immobilisation. In the presence of 2 % PEG400, SBA-15-Ni-cyclam showed 78.7 % uptake of available protein while unmodified SBA-15 showed only 4.3 % uptake of available protein. In order to demonstrate activity of a histidine-tagged immobilised enzyme, histidine-tagged alanine Racemase (His6-AlaR) was immobilised onto the nickel and cobalt functionalised mesoporous silicate, MCF. Non-specific binding of His6-AlaR onto unmodified MCF was reduced to 22.9 % and was achieved when His6-AlaR was immobilised onto nickel modified MCF in the presence of 2 % PEG400. Activity studies of Candida Antarctica lipase B (CALB) immobilised onto nickel and cobalt functionalised MCF were performed in order to assess their applicability as biocatalysts. Non-histidine tagged CALB displayed ~50 % non-specific immobilisation onto MCF, MCF-Ni and MCF-Co. This was ...